Assessing mortality associated with heatwaves in the cool climate region of Tasmania, Australia - Sharon L. Campbell; Nicolas Borchers-Arriagada; Grant J. Williamson; Fay H. Johnston (Elsevier, 2024)
Background: Anthropogenic climate change is causing a rise in global temperatures, with this trend projected to increase into the future. Heatwaves are associated with a rise in preventable deaths, however this association is less well understood in regions experiencing cooler climates. Methods: We used a space-time-stratified conditional Poisson (-quasi) regression analysis to assess if heatwaves were associated with all-cause mortality in Tasmania, Australia, for the period 2010-2018. Results: We found that across Tasmania, low-intensity heatwaves were relatively common, with less occurrence of severe and extreme heatwaves. We found that for all heatwave types combined, there was a rise in mortality of 8 % (RR=1.08, 95 %CI 1.01-1.16). For low-intensity heatwaves, we found mortality increased by 9 % (RR=1.09, 95 %CI 1.02-1.17). Conclusion: These results have health promotion and health protection policy and practice implications for Tasmanian healthcare services, and potentially other cooler climate regions around the world.